Adaptation of Chronic Kidney Disease-Self Management Knowledge Tool (CKD-SMKT) into Turkish - OKUYAN, BETÜL; ARIKAN, İZZET HAKKI; SANCAR, MESUT; ALTIPARMAK, ÖZNUR (MARMARA UNIV, INST HEALTH SCIENCES, 2021)
Objective: The aim of the study is adaptation of Chronic Kidney Disease-Self Management Tool (CKD-SMKT) into Turkish language. Methods: The study was conducted with chronic kidney disease patients in a training and research hospital. Initially, translation and cultural adaptation of the Turkish tool was performed, afterwards the internal consistency was evaluated with Kuder-Richardson (KR-20) coefficient. Results: The total of 48 patients (mean of age [years]: 62.13 +/- 15.19) were included the study. An acceptable internal consistency with a KR-20 value of 0.71 was determined for the tool. 62.5% of participants answered correctly to all self-management knowledge items, however only 10.4% of them indicated that they behaved in line with the correct answers of all self-management knowledge items. Conclusion: The Turkish version of CKD-SMKT is a reliable and appropriate tool to assess the self-management knowledge of chronic kidney disease patients.
Keywords: Chronic kidney disease; knowledge; self-management; HEALTH LITERACY; EFFICACY; INSTRUMENT; BEHAVIORS; CARE